Association of the P441L KCNQ1 variant with severity of long QT syndrome and risk of cardiac events - Lu, Haoyang; Ding, Wen; Xiao, Hui; Dai, Manyu; Xue, Yangcheng; Jia, Zhuoran; Guo, Jie; Wu, Mengzuo; Shen, Bing; Zhao, Ren (Frontiers in Cardiovascular Medicine, 2022)
Dysfunction of potassium voltage-gated channel subfamily Q member 1 (KCNQ1) is a primary cause of long QT syndrome type 1 (LQT1). Here, we report a novel missense mutation P441L in KCNQ1 C-terminus of a 37-year-old woman with severe LQT1 phenotype. Variant P441L transporting to the plasma membrane and interacting with KCNE1 were both markedly decreased, leading to potassium efflux disorder and eventually LQT1. Mutations between the C-terminal helix A and helix B of KCNQ1 have linked with low cardiac event risk, however, we firstly find variant P441L causing a severe LQT1 phenotype with a high risk of cardiac events.